Finite Element Analysis of CRH2 EMUs Contactor Box Based on ABAQUS - WANG Hong-bo; DENG Xue-shou; JIN Lei-bo (机车电传动)
To prove the structural strength of the contactor box meeting the requirement of train working environment, stress of CRH2EMUs contactor box under vibration impact was calculated by finite element analysis of ABAQUS, result of which could be a strong supportfor fatigue analysis and a theory basis for the modular design of CRH2 EMUs contactor box.